REAL-TIME DISTRIBUTION SYSTEM ANALYSIS AND LOAD MANAGEMENT ALGORITHM FOR MINIMIZING HARMONICS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper presents a detailed analysis of the selected distribution network consisting of fifty-five 200KVA transformers and thirty 100KVA transformers. These units are observed five times during the period of one year based on balanced and unbalanced conditions. Detailed power loss analysis has been discussed with an innovative switching algorithm of phase balancing. The switching algorithm is applied on the experimental test bench. This solution provides ease of complete switching between the phases along with that it monitors the real-time data and keeps a record of current flowing on each phase of the transformer.
Keywords: Distribution system; Power loss; Harmonics; Algorithm